ChemInform Abstract: Hexagonal RMnO3: A Model System for Two‐dimensional Triangular Lattice Antiferromagnets. Issue 31 (14th July 2016) - Sim, Hasung; Oh, Joosung; Jeong, Jaehong; Le, Manh Duc; Park, Je‐Geun
Abstract: Review: 121 refs.